An Analysis on Enhance Reading and Effect of Non-Government Organizations In Capacity Improvement: Exploring the Role and Scope of NGOs in Capacity Building (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Manydiverse types of bodies are now described as being NGOs. There is no generallyaccepted definition of an NGO and the term carries different connotations indifferent circumstances. Nevertheless, there are some fundamental features.Clearly an NGO must be independent from the direct control of any government.In addition, there are three other generally accepted characteristics thatexclude particular types of bodies from consideration. An NGO will not beconstituted as a political party; it will be non-profit making and it will benot be a criminal group, in particular it will be non-violent. Thesecharacteristics apply in general usage, because they match the conditions forrecognition by the United Nations. The boundaries can sometimes be blurred:some NGOs may in practice be closely identified with a political party; manyNGOs generate income from commercial activities, notably consultancy contractsor sales of publications; and a small number of NGOs may be associated withviolent political protests. Nevertheless, an NGO is never constituted as agovernment bureaucracy, a party, a company, a criminal organization or aguerrilla group. Thus, for this article, an NGO is defined as an independentvoluntary association of people acting together on a continuous basis, for somecommon purpose, other than achieving government office, making money or illegalactivities. This basic approach will be elaborated and modified below.